FORESIGHT TECHNOLOGIES USAGE IN WORKING OUT LONG TERM. FORECASTS OF SERVICE AND TOURISM PERSONNEL TRAINING SYSTEM DEVELOPMENT - ZAITSEVA, Natalia A.; LARIONOVA, Anna A.; MINERVIN, Igor G.; YAKIMENKO, Ruslan V.; BALITSKAYA, Irina V. (Journal of Environmental Management and Tourism; Vol 6 No 2 (2015): JEMT Volume VI Issue 2(12) Winter 2015, 2016)
The present article deals with the questions of working out Service and Tourism personnel training system changing forecast on the base of the usage of foresight techniques as actual instrument of social and economic processes forecasting for societies and economics of different countries.The technique allows us not only to estimate the present situation and highlight the main trends which give an actual picture of the present but to reveal threats and possibilities which may appear in the market in near future, and, moreover, to prepare the projects aiming at these threats prevention and at new positive possibilities developing. In Russia ‘Rapid Foresight’ technique was worked out by Agency of Strategic Initiative and now it is quite actively used. Several Profession Atlas versions showing expert opinions of professional societies about the changes which may appear in the structure and quality of personnel in different spheres in remote future were developed with the helpof Rapid Foresight Technology usage. With the help of ‘Rapid Foresight’ technique perspectives for education and service sphere professions and personnel competencies were developed. On the base of the present technique the authors of the article have carried out an investigation on robotization trend in service and tourism spheres. The investigation showed that the opinions of employers and educational institutes’ representatives are splitted into two equal parts: one half thinks that in service robotization will prevail and the other half says that the human factor will predominate. Hence, the results of New York Federal Reserve Bank investigation, which forecasted the growth of non-routine labor and connected with that crucial necessity for such catering, service, hospitality and tourism personnel competencies as thought flexibility, ability to settle non-typical problems and use of creative approach in servicing clients. The materials of the article have a practical value for educational institutes, engaged in training of Service and Tourism personnel, and for Service and Tourism enterprises themselves.
Keywords: Education; personnel; service; tourism; development forecast; competence; foresight